Atezolizumab plus bevacizumab and chemotherapy as first-line therapy for cervical cancer: a cost-effectiveness analysis in the US - Lin, Yingtao; Li, Cijuan; Wang, Chang; Chen, Jian; Huang, Yuanqing (Frontiers in Immunology, 2024)
ObjectiveMedication is the predominant therapy for advanced cancers. However, the use of novel anticancer medications is a major contributor to disease-related financial hardships. Recently, numerous countries have mandated the pharmacoeconomic assessments of novel oncological agents to mitigate patient financial risks and optimize resource allocation. The present study evaluated the cost-effectiveness of adding atezolizumab to standard therapy (atezolizumab plus bevacizumab [BC]) for metastatic, persistent, and recurrent cervical cancer from the perspective of US healthcare payers, with the aim of supporting policymaking and promoting the rational use of healthcare resources.MethodsUsing clinical efficacy and safety data from the BEATcc clinical trial, in addition to cost and utility values from publicly available databases and published literature, a partitioned survival model over a 20-year lifetime horizon was developed to assess the cost-effectiveness of atezolizumab plus bevacizumab and chemotherapy (ABC) versus BC. The primary output of the model was the incremental cost-effectiveness ratio (ICER) and sensitivity analyses were performed to assess its robustness.ResultsAt both 20 and 4.5 y of time horizon, ABC therapy showed poor cost-effectiveness, with ICER of 193926.48/QALY and 168482.26/QALY, respectively, which were higher than the 150,000/QALY willingness-to-pay threshold. One-way sensitivity analysis showed that the price of atezolizumab had the most significant impact on the model results. When the price of atezolizumab was reduced by 10%, ABC changed from being not cost-effective to cost-effective (ICER = 121531.24/QALY). Probabilistic sensitivity analysis showed a 32.6% probability that ABC would be cost-effective, which increased to 58.6% when the price of atezolizumab was reduced by 10%.ConclusionsFor patients with metastatic, persistent, and recurrent cervical cancer in the US, ABC was not as cost-effective as BC. Appropriate price reduction (10%) is recommended for atezolizumab to improve cost-effectiveness of ABC therapy.